Countering counterterrorism: defending human rights and challenging curfews in Turkey. (20th October 2021) - Negrón-Gonzales, Melinda
ABSTRACT: Turkey imposed open-ended blanket curfews beginning in 2015, resulting in gross human rights violations. This article analyzes strategies employed by domestic activists to address violations. It explains what worked, what did not, and why. It argues that longstanding barriers to mass mobilization, including some that predate de-Europeanization, shaped activists' mobilization strategies. Because of an unfavorable domestic environment, activists used a boomerang strategy, disseminating information to international allies who applied pressure to Turkish officials. This strategy effectively mobilized transnational human rights networks, resulting in a continuous and concerted effort by international actors to persuade Turkish officials to protect human rights while countering terrorism. Nevertheless, the boomerang strategy and a legal strategy to file applications with the European Court of Human Rights ultimately failed to generate a shift in policy. The article concludes with a discussion about the factors that contributed to this outcome.